Features of a concept “Woman” in the turkic people (Journal of Oriental Studies, 2016)
One of key concepts of any culture is the concept ‘woman’. It represents a projection of stereotypic ideas of the woman, as about the carrier of socially ordered qualities and the properties created on the basis of roles, carried out by the woman in society.
Keywords: consept; Turkic people; culture; society.